Effective orifice area and hemodynamic performance of the transcatheter Edwards Sapien 3 prosthesis: short-term and 1-year follow-up. (8th January 2017) - Külling, Mischa; Külling, Jeremy; Wyss, Christophe; Hürlimann, David; Reho, Ivano; Salzberg, Sacha; Bühler, Ines; Noll, Georg; Grünenfelder, Jürg; Corti, Roberto; Biaggi, Patric
Abstract: Aims: The Edwards Sapien 3 heart valve prosthesis (S3) is commonly used for transcatheter aortic valve implantation (TAVI) and is available in three sizes. To date no data has been published on the effective orifice area (EOA) and the hemodynamic performance of the three different S3 sizes. The aim of this study was to measure the size-specific EOA and hemodynamic performance of the S3 in short-term and 1-year follow-up. Methods and results: One hundred and thirteen consecutive patients treated by TAVI with a S3 prosthesis at the Heart Clinic Zurich between May 2014 and July 2015 were included. Clinical data were extracted from the Swiss TAVI registry. The EOA was calculated using Doppler echocardiography (peri-interventionally and at discharge) and by 3D-biplane transoesophageal echocardiography (peri-interventionally). Mean transvalvular gradients (dPmean) were additionally calculated with Doppler echocardiography at 30 days and 1 year. Results were analysed separately for the 23 mm ( n = 42; 37%), 26 mm ( n = 46; 41%), and 29 mm ( n = 25; 22%) prostheses. At discharge, the EOAs were 1.6 ± 0.2 cm 2 (23 mm S3), 2.0 ± 0.2 cm 2 (26 mm S3), and 2.7 ± 0.2 cm 2 (29 mm S3), p < 0.001. The dPmeans at discharge were 10.9 ± 6.0 mmHg (23 mm S3), 10.4 ± 3.5 mmHg (26 mm S3), and 8.9 ± 2.8 mmHg (29 mm S3), p = 0.235, and did not significantly change over time within any of the S3 sizes. Conclusions: Post-TAVI, the EOAs of the three different S3 prosthesis sizes differ significantly, the transvalvular gradients, however, are comparable. Mean transvalvular gradients remain stable over time and document good prosthesis function after 1 year.